Sn-Y type molecular sieve, method for producing the same, and use thereof, as well as method for the oxidation reaction of cyclic ketones.
Patent Information
- Application Number
- JP2026520150
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-02-20
- Filing Date
- 2024-12-25
- Publication Date
- 2026-10-16
Smart Images

Figure 2026534545000001 
Figure 2026534545000002 
Figure 2026534545000003
Abstract
Description
Detailed description of the invention
[0001] [Cross-reference of related applications] This application claims the interests of Chinese Patent Application No. 202410187144.6, filed on 20 February 2024, the contents of which are incorporated herein by reference.
[0002] [Technical Field] This invention relates to the field of molecular sieve synthesis, and more specifically to Sn-Y type molecular sieves, methods for producing the same, and uses, as well as methods for the oxidation reaction of cyclic ketones.
[0003] [Background technology] Heteroatom molecular sieves are molecular sieves containing other elements, formed by isomorphically substituting some silicon, aluminum, or phosphorus atoms in the molecular sieve framework with heteroatoms. Because the introduction of heteroatoms into the molecular sieve framework often alters the inherent structure and properties of the molecular sieve (e.g., acidity, particle size, channel properties), the limitations of conventional silicon-aluminum molecular sieves have been gradually overcome in recent years, expanding the application fields of molecular sieves. The synthesis of heteroatom molecular sieves is considered an important area of molecular sieve synthesis, possessing potential commercial value and attracting increasing attention.
[0004] Since the successful synthesis of the TS-1 molecular sieve, various heteroatom molecular sieves (e.g., tin, iron, gallium, zirconium, vanadium, etc.) have been manufactured. Among these, the synthesis of tin-based molecular sieves has attracted considerable attention. Because Sn is embedded in the molecular sieve skeleton, it provides a unique Lewis acid center to the molecular sieve, enabling it to catalyze the Bayer-Villiger reaction of ketones. The Sn-beta molecular sieve was synthesized in 1997 and used as a catalyst for the Bayer-Villiger reaction of cyclohexanone in 2001, and the catalyst exhibits excellent selectivity for the product, ε-caprolactone. However, in the Bayer-Villiger reaction of cyclohexanone, a certain concentration of hydrogen peroxide is usually used as the oxidizing agent, so water is inevitably introduced during the reaction. This water is adsorbed onto the active center Sn, causing problems of reduced catalytic performance and increased by-products. Therefore, in recent years, using solvents containing tert-butyl hydroperoxide as oxidizing agents instead of hydrogen peroxide has become a new trend. However, because the tert-butyl hydroperoxide molecule is relatively large, the diffusion-restricting effect of the Sn-β molecular sieve channels is very pronounced, and the effect is not ideal for practical applications. Since the Y molecular sieve has more open channels and a supercage structure, reports on the synthesis of Sn-Y molecular sieves have been published in recent years.
[0005] Zhiguo Zhu et al. reported a method for synthesizing Sn-Y molecular sieves in their article "Postsynthesis and Effective Baeyer-Villiger Oxidation Properties of Hierarchical FAU-type Stannosilicate" in Volume 120 of the Journal of Physical Chemistry C. In this method, a USY molecular sieve is first prepared, then the USY powder is placed in an aqueous (NH4)2SnCl6 solution, hydrochloric acid solution is added to control the pH of the reaction, and the reaction is carried out at a constant temperature with stirring for a certain period of time to obtain the Sn-Y molecular sieve. However, the tin skeleton of the molecular sieve synthesized by this method is mainly distributed inside the molecular sieve, which is unfavorable for contact between the active site of the Sn species and the reacting molecules during the reaction.
[0006] In their paper "Postsynthesis of FAU-type stannosilicate as efficient heterogeneous catalyst for Baeyer-Villiger oxidation" published in Volume 519 of *APPLIED CATALYSIS A-GENERAL*, Zhiguo Zhu et al. reported a method for synthesizing Sn-Y molecular sieves. This method involves using USY molecular sieves as a starting material, first treating the USY with acid, and then reacting the dealuminized USY with SnCl4 at high temperature to implant Sn into the USY molecular sieves. However, in Sn-Y molecular sieves synthesized by this method, most of the Sn atoms are distributed inside the molecular sieve, and the Sn is not completely exposed, which is unfavorable for contact between the active site of the Sn species and the reactant molecules during the reaction.
[0007] [Summary of the Invention] [Problems the invention aims to solve] This invention provides a Sn-Y type molecular sieve, a method for producing the same, and a method for the oxidation reaction of cyclic ketones, in order to overcome the shortcomings of the prior art. The Sn-Y type molecular sieve according to this invention has Sn mainly concentrated on the outer surface of the Y type molecular sieve and exhibits superior activity and selectivity for the Bayer-Villiger oxidation reaction of cyclic ketones.
[0008] [Means for solving the problem] A first aspect of the present invention provides a Sn-Y type molecular sieve having a surface silicon-tin molar ratio of 50 to 70 and a bulk silicon-tin molar ratio of 200 to 300.
[0009] Preferably, the molecular sieve has an L-acid content of 100 to 200 μmol / g, more preferably 130 to 170 μmol / g, as measured by pyridine adsorption infrared spectroscopy at a desorption temperature of 200°C.
[0010] In the Sn-Y type molecular sieve according to the present invention, the skeletal Sn species are mainly concentrated on the outer surface of the Y type molecular sieve, and the number of Sn species inside is relatively small. As a result, the Lewis acid moieties of the Sn-Y type molecular sieve according to the present invention are mainly concentrated on the surface of the molecular sieve, resulting in better proximity to the reactant molecules, virtually no constraints on the diffusion rate during the reaction, and effective utilization as Sn species that provide Lewis acid moieties.
[0011] A second aspect of the present invention provides a method for producing a Sn-Y type molecular sieve, the method being: Step 1) involves subjecting a NaY molecular sieve to solid-phase ion exchange with an ammonium salt, and then roasting it to obtain an HY molecular sieve. Step 2) involves subjecting the HY molecular sieve to solid-phase ion exchange with a tin source to obtain a Y molecular sieve after Sn ion exchange, The process includes step 3) treating the Y molecular sieve after Sn ion exchange in a mixed gas containing water vapor and oxygen gas, and then acid treating it.
[0012] The method according to the present invention first involves an ammonium salt and Na + Solid-phase ion exchange is performed using this method, and the Na on the outer surface of the Y molecular sieve + These are exchanged for quaternary ammonium cations. These quaternary ammonium cations are then converted to H during subsequent roasting. + It is converted to Sn using solid-phase ion exchange. 2+ The outer surface of the Y molecular sieve is replaced. Subsequently, high-temperature treatment is performed using a mixed gas of water vapor and oxygen to create vacancies on the outer surface by dealuminization, and Sn ions are inserted into the vacancies on the outer surface of the molecular sieve to form a four-coordinate skeleton Sn. Finally, the objective of concentrating Sn species containing L acid on the outer surface of the molecular sieve is achieved.
[0013] A third aspect of the present invention provides the use of the Sn-Y type molecular sieve described in the first aspect in the oxidation reaction of cyclic ketones.
[0014] A fourth aspect of the present invention provides a method for the oxidation reaction of a cyclic ketone, the method comprising the step of reacting a cyclic ketone with an oxidizing agent under oxidation conditions and in the presence of a solvent and a catalyst, wherein the catalyst is the Sn-Y type molecular sieve described in the first aspect.
[0015] The Sn-Y type molecular sieve according to the present invention exhibits superior activity for the oxidation reaction of cyclic ketones, and has relatively high selectivity and yield for the reaction product, lactone. Furthermore, the method for producing the Sn-Y type molecular sieve used in the present invention is simple to operate, has low manufacturing costs, and is suitable for industrial production needs.
[0016] [Modes for carrying out the invention] The endpoints and any values of the ranges disclosed herein are not limited to their exact ranges or values, and these ranges or values should be understood as including values close to them. For numerical ranges, one or more new numerical ranges can be obtained by combining the endpoint values of each range, the endpoint values of each range with individual point values, and individual point values with each other. These new numerical ranges are deemed to be specifically disclosed herein.
[0017] In this invention, unless otherwise specified, all percentages and percentage contents are based on mass.
[0018] A first aspect of the present invention provides a Sn-Y type molecular sieve, wherein the molecular sieve has a surface silicon-tin molar ratio of 50 to 70 and a bulk silicon-tin molar ratio of 200 to 300. For example, the surface silicon-tin molar ratio of the molecular sieve is 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, more preferably 55 to 65. For example, the bulk silicon-tin molar ratio of the molecular sieve is 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, more preferably 230 to 280.
[0019] The Sn-Y type molecular sieve according to the present invention has a smaller surface silicon-tin molar ratio, and tin species are mainly distributed on the outer surface of the molecular sieve, which is further advantageous for improving the utilization rate of Sn, and further has higher catalytic performance when applied to the oxidation reaction of cyclic ketones.
[0020] In the present invention, the term "Sn-Y type molecular sieve" does not specifically limit the properties and structure of the product according to the present invention. As long as the Y-type molecular sieve contains the Sn element, and the surface silicon-tin molar ratio and the bulk silicon-tin molar ratio meet the requirements of the present invention, they are included in the protection scope of the present invention.
[0021] The crystal form of the molecular sieve can be determined by XRD characterization.
[0022] According to the present invention, preferably, the bulk SiO2 / Al2O3 molar ratio of the molecular sieve is 60 to 140, preferably 80 to 120, for example, 80, 90, 100, 110, or 120.
[0023] According to the present invention, preferably, the surface SiO2 / Al2O3 molar ratio of the molecular sieve is 350 to 700, preferably 420 to 630, for example, 420, 450, 500, 530, 550, 580, 600, or 630.
[0024] In the present invention, the surface silicon-tin molar ratio and the surface silicon-aluminum molar ratio of the molecular sieve are characterized by X-ray photoelectron spectroscopy (XPS). Specifically, the XPS characterization is performed using a Kratos Axis Ultra X-ray photoelectron spectrometer with Al Kα (1486.6 eV) as the excitation source. The binding energy of the XPS spectrum is corrected with C 1s (284.8 eV), and then the surface silicon-tin molar ratio and the silicon-aluminum molar ratio of the molecular sieve are obtained through conversion.
[0025] In this invention, the silicon-tin molar ratio and SiO2 / Al2O3 molar ratio of the bulk molecular sieve are measured using inductively coupled plasma atomic emission spectroscopy (ICP-AES). Before testing, the solid powder of the molecular sieve is pretreated. The powder is added to a mixed solution of water, nitric acid, and hydrofluoric acid, heated at 150°C until the sample is completely dissolved and clear, cooled, transferred to a volumetric flask, diluted to the final volume with deionized water, and shaken well. Then, quantitative analysis is performed using the standard curve method. Finally, the measured corresponding elemental content is converted into silicon-aluminum molar ratio (SiO2 / Al2O3) and silicon-tin molar ratio (SiO2 / SnO2).
[0026] According to the present invention, preferably, the molecular sieve has an L-acid content of 100 to 200 μmol / g at a desorption temperature of 200°C, measured by pyridine adsorption infrared spectroscopy, for example, 100 μmol / g, 110 μmol / g, 120 μmol / g, 130 μmol / g, 140 μmol / g, 150 μmol / g, 160 μmol / g, 170 μmol / g, 180 μmol / g, 190 μmol / g, 200 μmol / g, preferably 130 to 170 μmol / g. The molecular sieve according to the present invention has a higher L-acid content at a desorption temperature of 200°C, measured by pyridine adsorption infrared spectroscopy.
[0027] According to the present invention, preferably, the molecular sieve has an L-acid / B-acid content ratio of 90 to 130, for example, 90, 100, 110, 120, 130, preferably 110 to 120, as measured by pyridine adsorption infrared spectroscopy at a desorption temperature of 200°C. Using a molecular sieve with an appropriate L-acid / B-acid content ratio is further advantageous in improving the conversion rate and selectivity of the target product during the reaction.
[0028] In the present invention, the contents of L acid and B acid in the molecular sieve are measured by pyridine adsorption infrared spectroscopy. Specifically, a sample is fabricated into a self-supporting sheet, heated to 500°C and held for 2 hours, then evacuated. After the sample is naturally cooled to room temperature, pyridine is adsorbed at room temperature for 30 minutes. Thereafter, the temperature is raised to 200°C, and evacuation is performed to remove the adsorbed pyridine molecules. The pyridine adsorption infrared spectrum at this temperature is recorded. In the pyridine adsorption infrared spectrum, 1450cm -1 The peak at is assigned to the absorption peak of L acid, and 1545cm -1 The peak at is assigned to the absorption peak of B acid. By integrating the peak area of the spectrum, the contents of L acid and B acid are obtained by infrared spectroscopy.
[0029] The quantitative calculation of L acid is performed by the following formula.
[0030] [Formula] I A is the integrated area of the absorption peak at 1450cm in the spectrum, a and m are respectively the area and mass of the self-supporting sample sheet, E is the integrated molar extinction coefficient, and E=1.42cm / μmol. -1 is the integrated area of the absorption peak at 1450cm in the spectrum, a and m are respectively the area and mass of the self-supporting sample sheet, E is the integrated molar extinction coefficient, and E=1.42cm / μmol.
[0031] The quantitative calculation of B acid is performed by the following formula.
[0032] [Formula] I A is the integrated area of the absorption peak at 1545cm in the spectrum, a and m are respectively the area and mass of the self-supporting sample sheet, E is the integrated molar extinction coefficient, and E=1.95cm / μmol. -1 is the integrated area of the absorption peak at 1545cm in the spectrum, a and m are respectively the area and mass of the self-supporting sample sheet, E is the integrated molar extinction coefficient, and E=1.95cm / μmol.
[0033] According to the present invention, preferably, the specific surface area of the molecular sieve is 770~850m 2 / g, preferably 790-830m 2 It is / g.
[0034] According to the present invention, preferably, the pore volume of the molecular sieve is 0.36 to 0.43 mL / g, more preferably 0.37 to 0.41 mL / g.
[0035] The molecular sieve according to the present invention has a relatively large specific surface area and a relatively large pore volume. In this invention, the specific surface area and pore volume of the molecular sieve are measured by the N2 adsorption / desorption method. Before measurement, the sample is first pretreated at 300°C for 3 hours, and then tested by adsorbing nitrogen gas at 77K. The specific surface area of the molecular sieve is calculated using the BET method, and the total pore volume is calculated as p / p 0 It is measured at =0.98.
[0036] According to the present invention, the relative crystallinity of the molecular sieve is preferably 86-96%, more preferably 89-93%. The molecular sieve according to the present invention has a higher crystallinity, which is further advantageous in improving its performance when used in catalytic oxidation reactions of cyclic ketones.
[0037] In this invention, the relative crystallinity of a Sn-Y molecular sieve sample is measured using an X-ray diffraction method, specifically the method of the Chinese Petrochemical Industry Standard SH / T 0340-92.
[0038] All molecular sieves having the aforementioned characteristics of the present invention can achieve the objectives of the present invention, but there are no particular requirements for their manufacturing method. According to a preferred embodiment of the present invention, a second aspect of the present invention provides a method for manufacturing a Sn-Y type molecular sieve, the method being Step 1) involves subjecting a NaY molecular sieve to solid-phase ion exchange with an ammonium salt, and then roasting it to obtain an HY molecular sieve. Step 2) involves subjecting the HY molecular sieve to solid-phase ion exchange with a tin source to obtain a Y molecular sieve after Sn ion exchange, The process includes step 3) treating the Y molecular sieve after Sn ion exchange in a mixed gas containing water vapor and oxygen gas, and then acid treating it.
[0039] In the present invention, the NaY molecular sieve raw material may be a commercially available product or any NaY molecular sieve manufactured by prior art. Preferably, in step 1), the mass fraction of Na2O in the NaY molecular sieve is 10.5 to 12%, preferably 10.8 to 11.7%. Preferably, the SiO2 / Al2O3 molar ratio of the NaY molecular sieve is 4.8 to 5.7, preferably 5.0 to 5.5.
[0040] According to the method of the present invention, the Na2O content in the molecular sieve is measured by X-ray fluorescence (XRF).
[0041] In the present invention, the ammonium salt has a relatively broad range of selectivity and only needs to be able to undergo an ammonium exchange reaction with the NaY molecular sieve. The ammonium salt may be inorganic ammonium, organic ammonium, or a mixture of both, and is preferably organic ammonium. To further improve the catalytic performance of the molecular sieve produced, preferably the ammonium salt is at least one selected from organic quaternary ammonium salts. The anion of the organic quaternary ammonium salt may include, but is not limited to, bromide ions and / or chloride ions, and may also be halogen ions. In the present invention, the group bonded to N also has a relatively broad range of selectivity and may be, for example, a C1-C5 alkyl group, and the four alkyl groups bonded to N may be the same or different.
[0042] According to a preferred embodiment of the present invention, the ammonium salt is at least one selected from tetramethylammonium bromide, tetramethylammonium chloride, tetraethylammonium bromide, tetraethylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium chloride, propyltrimethylammonium bromide, and propyltrimethylammonium chloride, more preferably tetramethylammonium bromide and / or tetramethylammonium chloride. Adopting this preferred embodiment is, firstly, even more advantageous in preferentially exchanging sodium ions on the outer surface of the molecular sieve.
[0043] In this invention, the solid-phase ion exchange is used to exchange Na ions in a NaY molecular sieve for ammonium ions in an ammonium salt. The solid-phase ion exchange has the conventional meaning in the art, specifically referring to an exchange performed under solid-phase conditions in which no solvent (e.g., water) is present during the exchange process. In the course of their research, the inventors subjected a NaY molecular sieve to solid-phase ion exchange with an ammonium salt and controlled the solid-phase ion exchange conditions, thereby exchanging the Na ions on the outer surface of the NaY molecular sieve. + The ions can be preferentially exchanged for quaternary ammonium cations, and when combined with other steps of the present invention, the objective of concentrating Sn species having L acid on the outer surface of the molecular sieve can be achieved more advantageously.
[0044] According to the present invention, preferably, the mass ratio of the amount of ammonium salt to the amount of NaY molecular sieve used is 0.04 to 0.14, and preferably 0.07 to 0.1.
[0045] According to a preferred embodiment of the present invention, in order to more uniformly mix the ammonium salt and the NaY molecular sieve, it is preferable to first grind the ammonium salt and the NaY molecular sieve in an inert atmosphere (e.g., a glove box) before the solid-phase ion exchange.
[0046] According to the present invention, preferably, the conditions for the solid-phase ion exchange in step 1) include a reaction temperature of 140 to 190°C, preferably 160 to 170°C, and a reaction time of 60 to 180 min, preferably 100 to 140 min, under an inert atmosphere. The inert atmosphere is provided by an inert gas commonly used in the art, and the inert atmosphere is preferably selected from nitrogen gas, helium gas, argon gas, or a mixture of any proportion thereof.
[0047] According to one specific embodiment of the present invention, the solid-phase ion exchange is performed in a state in which an inert gas is flowing.
[0048] According to a preferred embodiment of the present invention, step 1) involves placing a NaY molecular sieve and an ammonium salt into a reactor, introducing an inert gas from one end of the reactor and exhausting the other end to maintain the flow of the inert gas in the reactor, and carrying out the reaction at the solid-phase ion exchange temperature.
[0049] According to the present invention, the specific method for the solid-phase ion exchange in step 1) is not particularly limited and can be carried out in a tubular reactor.
[0050] Preferably, the method further includes the step of washing, filtering, and drying the solid product obtained by solid-phase ion exchange before the roasting in step 1). The present invention does not particularly limit the conditions for washing, filtering, and drying, and those skilled in the art can select these conditions using the prior art.
[0051] According to the present invention, the roasting conditions in step 1) have a relatively wide range of selection, and the quaternary ammonium cation is H in the roasting process. + This can be converted to the following. Preferably, the roasting conditions in step 1) include a roasting temperature of 500-550°C and a roasting time of 3-6 hours in an oxygen-containing atmosphere. The present invention does not particularly limit the oxygen-containing atmosphere, and may be, for example, air.
[0052] According to the present invention, preferably the method further includes the step of independently drying and / or roasting the NaY molecular sieve and the ammonium salt before performing the solid-phase ion exchange. Removing water contained in the NaY molecular sieve and the ammonium salt by drying and / or roasting them is further advantageous in ensuring that step 1) is carried out under water-free conditions. Preferably, the ammonium salt is dried and the NaY molecular sieve is roasted. More preferably, the conditions for roasting the NaY molecular sieve include a roasting temperature of 500-550°C and a roasting time of 3-6 hours. More preferably, the conditions for drying the ammonium salt include a drying temperature of 100-120°C and a drying time of 4-7 hours.
[0053] According to the present invention, in step 2), in order to more uniformly mix the HY molecular sieve and the tin source, preferably in step 2), before performing the solid-phase ion exchange, the HY molecular sieve and the tin source are first pulverized in an inert atmosphere (e.g., a glove box).
[0054] In Step 2), the specific operating method for the solid-phase ion exchange and the range of reactor selection may be as described in Step 1), but will not be explained in detail here.
[0055] According to the present invention, preferably in step 2), the mass ratio of the tin source to the HY molecular sieve is 0.07 to 0.15, preferably 0.1 to 0.12. When this preferred embodiment is adopted, Sn 2+ This is even more advantageous for replacing the outer surface of the Y molecular sieve.
[0056] According to the present invention, preferably, the conditions for the solid-phase ion exchange in step 2) include a reaction temperature of 250 to 350°C, preferably 270 to 330°C, and a reaction time of 60 to 180 min, preferably 100 to 140 min, under an inert atmosphere. The selection range of the inert atmosphere may be as described above.
[0057] According to the present invention, preferably, the tin source is an anhydrous tin source, more preferably a divalent tin source, and even more preferably at least one of stannous chloride, stannous sulfate, and stann(II) acetate.
[0058] Preferably, the method further includes, before step 3), washing, filtering, and drying the solid product obtained by solid-phase ion exchange in step 2). The present invention does not particularly limit the conditions for washing, filtering, and drying, and those skilled in the art can select these conditions using the prior art.
[0059] According to the present invention, preferably in step 3), the molar ratio of water vapor to oxygen gas in the mixed gas is 7 to 9, preferably 7.5 to 8.5. Adopting this preferred embodiment is further advantageous for embedding tin in the Y molecular sieve framework.
[0060] According to the present invention, preferably in step 3), the conditions for processing in a mixed gas containing water vapor and oxygen gas include a reaction temperature of 550 to 650°C, preferably 580 to 620°C, a processing time of 1 to 4 hours, preferably 2 to 3 hours, and preferably a total pressure of 0.05 to 0.15 MPa, preferably 0.08 to 0.12 MPa.
[0061] According to one preferred specific embodiment of the present invention, the step of treating the Sn ion-exchanged Y molecular sieve in a mixed gas containing water vapor and oxygen gas includes the steps of introducing the mixed gas containing water vapor and oxygen gas into a reactor (e.g., a tubular furnace reactor), then treating the Sn ion-exchanged Y molecular sieve under treatment temperature and pressure, stopping the introduction of gas after the treatment is complete, removing the sieve after cooling, and performing the acid treatment.
[0062] The present invention does not particularly limit the specific conditions and operating methods of the acid treatment in step 3), and the acid treatment in step 3) can remove aluminum from the molecular sieve. In the present invention, the type of acid used in the acid treatment in step 3) has a relatively broad range of selection and may be an inorganic acid and / or an organic acid, preferably an inorganic acid. The inorganic acid is preferably at least one of nitric acid, hydrochloric acid, and sulfuric acid. The organic acid is preferably at least one of citric acid, oxalic acid, EDTA, and tartaric acid.
[0063] According to the present invention, preferably, the acid concentration used in the acid treatment is 0.2 mol / L to 0.4 mol / L, more preferably 0.25 to 0.35 mol / L.
[0064] According to the present invention, preferably, the conditions for the acid treatment include a treatment temperature of 30 to 60°C, preferably 40 to 50°C, a treatment time of 60 to 180 min, preferably 100 to 140 min, and a solid-liquid mass ratio of 1:6 to 1:12, preferably 1:8 to 1:10 during the acid treatment. In the present invention, the number of times the acid treatment is performed is not particularly limited and may be once or two or more times, but preferably one to two times.
[0065] Preferably, the method further includes, after the acid treatment in step 3), washing, filtering, and drying the solid product obtained by the acid treatment. The present invention does not particularly limit the conditions for washing, filtering, and drying, and those skilled in the art can select these conditions using the prior art. The preferred drying conditions include a temperature of 120 to 160°C and a time of 4 to 6 hours.
[0066] According to the present invention, preferably, in molecular sieves produced by subjecting a NaY molecular sieve to solid-phase ion exchange with an ammonium salt and an HY molecular sieve to solid-phase ion exchange with a tin source, the surface silicon-tin molar ratio is 50 to 70, and the bulk silicon-tin molar ratio is 200 to 300.
[0067] A third aspect of the present invention provides the use of the Sn-Y type molecular sieve described in the first aspect above in oxidation reactions of cyclic ketones. The Sn-Y type molecular sieve according to the present invention has relatively high performance in oxidation reactions of cyclic ketones, particularly in the Bayer-Villiger oxidation reaction. Preferably, the use of the Sn-Y type molecular sieve in the Bayer-Villiger oxidation reaction of cyclic ketones. The Sn-Y type molecular sieve of the present invention is suitable for oxidation reactions of at least one of various cyclic ketones, such as cyclohexanone, 2-adamantanone, dihydrocarbone, and bicyclo[3,2,0]hepta-2-en-6-one, and preferably, the use of the Sn-Y type molecular sieve in oxidation reactions of cyclohexanone or 2-adamantanone.
[0068] A fourth aspect of the present invention provides a method for the oxidation reaction of a cyclic ketone, the method comprising the step of reacting a cyclic ketone with an oxidizing agent under oxidation conditions and in the presence of a solvent and a catalyst, wherein the catalyst is the Sn-Y type molecular sieve described in the first aspect.
[0069] Preferably, the cyclic ketone is at least one of cyclohexanone, 2-adamantanone, dihydrocarbone, and bicyclo[3,2,0]hepta-2-en-6-one, more preferably cyclohexanone and / or 2-adamantanone.
[0070] In the present invention, the oxidizing agent has a relatively broad range of selectivity and only needs to be able to oxidize cyclic ketones, and may be a common choice in the art. Preferably, the oxidizing agent is at least one selected from tert-butyl hydroperoxide, hydrogen peroxide, cumene hydroperoxide, cyclohexyl hydroperoxide, peracetic acid, and perpropionic acid, preferably tert-butyl hydroperoxide.
[0071] In the present invention, the type of solvent has a relatively broad range of selection and only needs to be able to provide a reaction environment. Preferably, the solvent is at least one selected from 1,4-dioxane, decane, chlorobenzene, and benzyl alcohol.
[0072] Preferably, the molar ratio of the oxidizing agent to the cyclic ketone is 1:(1~3).
[0073] Preferably, the amount of catalyst used per 1 mmol of oxidizing agent is 80 to 600 mg, more preferably 80 to 300 mg.
[0074] Preferably, the conditions for the oxidation reaction include an oxidation reaction temperature of 75 to 95°C and an oxidation reaction time of 2 to 8 hours.
[0075] In this invention, unless otherwise specified, all percentages and percentage contents are based on mass.
[0076] The manufacturing method and product performance of the present invention will be further described below with reference to examples and comparative examples, but the following examples are not intended to limit the present invention.
[0077] In the molecular sieves of the following examples and comparative examples, the silicon-tin molar ratio on the surface is obtained by XPS testing, and the silicon-tin molar ratio of the bulk and the SiO2 / Al2O3 molar ratio of the molecular sieve are obtained by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The L acid and B acid content of the molecular sieve is measured using pyridine adsorption infrared spectroscopy. The specific surface area and pore volume of the molecular sieve are measured using N2 adsorption / desorption. The relative crystallinity of the molecular sieve is measured according to the method of the Chinese Petrochemical Industry Standard SH / T 0340-92. The Na2O content in the molecular sieve is measured using X-ray fluorescence (XRF). The specific conditions for each test method are as described in the above-mentioned embodiments for carrying out the invention and are therefore not described in detail here.
[0078] Example 1 NaY molecular sieves with a Na2O content of 12.0% (SiO2 / Al2O3 molar ratio of 4.8) were roasted at 500°C for 3 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Then, the NaY molecular sieves and tetramethylammonium bromide powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.042. The solid was then placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 185°C and the reaction was carried out for 70 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve after quaternary ammonium cation exchange was roasted at 530°C in air for 4 hours to obtain the HY molecular sieve. Then, the HY molecular sieve and anhydrous stannous chloride powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.07. The solid was then transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 345°C and the reaction was carried out for 60 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then the sieve was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. A Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 7.0 of water vapor and oxygen gas was introduced, and the reaction was carried out at 650°C for 1 hour. The total pressure in the reactor was controlled to 0.06 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain a Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.2 mol / L hydrochloric acid solution at 60°C for 170 minutes, controlling the solid-liquid mass ratio to 1:12 during treatment. A total of one treatment cycle was performed. After treatment, the solid was filtered and washed, and dried at 130°C for 4 hours to obtain the final Sn-Y molecular sieve product.
[0079] Example 2 NaY molecular sieves with a Na2O content of 10.6% (SiO2 / Al2O3 molar ratio of 5.7) were roasted at 520°C for 4 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Then, the NaY molecular sieves and tetramethylammonium bromide powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.13. The solid was then placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 144°C and the reaction was carried out for 170 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve, after quaternary ammonium cation exchange, was roasted at 520°C in air for 5 hours to obtain the HY molecular sieve. Subsequently, the HY molecular sieve and anhydrous stannous chloride powder were pulverized in a glove box and uniformly mixed, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.14. Then, the solid was transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 260°C and the reaction was carried out for 177 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then it was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. The Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 8.8 of water vapor and oxygen gas was introduced, and the reaction was carried out at 560°C for 3.5 hours. The total pressure in the reactor was controlled to 0.14 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain the Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.4 mol / L nitric acid solution at 35°C for 90 minutes, controlling the solid-liquid mass ratio to 1:7 during treatment. The treatment was repeated a total of two times. After treatment, the solid was filtered and washed, and dried at 150°C for 4 hours to obtain the final Sn-Y molecular sieve product.
[0080] Example 3 NaY molecular sieves with a Na2O content of 12.0% (SiO2 / Al2O3 molar ratio of 4.8) were roasted at 550°C for 6 hours, and tetramethylammonium bromide powder was dried at 120°C for 5 hours. Subsequently, the NaY molecular sieves and tetramethylammonium bromide powder were pulverized in a glove box and uniformly mixed, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.11. Then, the solid was placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 155°C and the reaction was carried out for 160 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then the sieves were removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve after quaternary ammonium cation exchange was roasted at 550°C in air for 6 hours to obtain the HY molecular sieve. Then, the HY molecular sieve and anhydrous stannous chloride powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.09. The solid was then transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 340°C and the reaction was carried out for 80 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then it was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. A Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 7.2 of water vapor and oxygen gas was introduced, and the reaction was carried out at 570°C for 4 hours. The total pressure in the reactor was controlled to 0.06 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain a Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.22 mol / L nitric acid solution at 55°C for 150 minutes, controlling the solid-liquid mass ratio to 1:11 during treatment. The treatment was repeated a total of two times. After treatment, the solid was filtered and washed, and dried at 150°C for 4 hours to obtain the final Sn-Y molecular sieve product.
[0081] Example 4 NaY molecular sieves with a Na2O content of 11.0% (SiO2 / Al2O3 molar ratio of 5.3) were roasted at 530°C for 5 hours, and tetramethylammonium bromide powder was dried at 110°C for 6 hours. Subsequently, the NaY molecular sieves and tetramethylammonium bromide powder were pulverized in a glove box and uniformly mixed, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.08. Then, the solid was placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 162°C and the reaction was carried out for 140 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve after quaternary ammonium cation exchange was roasted at 530°C in air for 5 hours to obtain the HY molecular sieve. Then, the HY molecular sieve and anhydrous stannous chloride powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.10. The solid was then transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 330°C and the reaction was carried out for 110 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then it was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. Sn(II)Y molecular sieves were placed in a tubular reactor, a mixed gas with a molar ratio of 8.3 of water vapor and oxygen gas was introduced, and the reaction was carried out at 615°C for 3 hours. The total pressure in the reactor was controlled to 0.09 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieves were removed to obtain Sn-Y molecular sieves. The obtained Sn-Y molecular sieves were treated in a 0.28 mol / L sulfuric acid solution at 43°C for 140 minutes, controlling the solid-liquid mass ratio to 1:10 during treatment. A total of one treatment cycle was performed. After treatment, the solid was filtered and washed, and dried at 140°C for 5 hours to obtain the final Sn-Y molecular sieve product.
[0082] Example 5 NaY molecular sieves with a Na2O content of 11.5% (SiO2 / Al2O3 molar ratio of 5.2) were roasted at 520°C for 5 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Subsequently, the NaY molecular sieves and tetramethylammonium bromide powder were pulverized in a glove box and uniformly mixed, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.10. Then, the solid was placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 170°C and the reaction was carried out for 110 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve after quaternary ammonium cation exchange was roasted at 530°C in air for 5 hours to obtain the HY molecular sieve. Then, the HY molecular sieve and anhydrous stannous chloride powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.12. The solid was then transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 290°C and the reaction was carried out for 135 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then it was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. A Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 7.7 of water vapor and oxygen gas was introduced, and the reaction was carried out at 585°C for 2 hours. The total pressure in the reactor was controlled to 0.12 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain a Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.35 mol / L hydrochloric acid solution at 50°C for 105 minutes, controlling the solid-liquid mass ratio to 1:8 during treatment. The treatment was repeated a total of two times. After treatment, the solid was filtered and washed, and dried at 140°C for 5 hours to obtain the final Sn-Y molecular sieve product.
[0083] Comparative Example 1 A NaY molecular sieve with a Na2O content of 12.0% (SiO2 / Al2O3 molar ratio of 4.8) was roasted at 500°C for 3 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Then, the NaY molecular sieve was added to distilled water, and the mass ratio of the NaY molecular sieve to the distilled water was controlled to 1:10. Subsequently, tetramethylammonium bromide was added, and the mass ratio of tetramethylammonium bromide to the NaY molecular sieve was controlled to 0.042. Then, ion exchange was performed once at 90°C for 70 minutes. After the ion exchange was completed, the sieve was removed, filtered, washed, and dried to obtain a Y molecular sieve after quaternary ammonium cation exchange. The Y molecular sieve after quaternary ammonium cation exchange was roasted at 530°C in air for 4 hours to obtain the HY molecular sieve. Then, the HY molecular sieve and anhydrous stannous chloride powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of anhydrous stannous chloride to HY molecular sieve to 0.07. The solid was then transferred to a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 345°C and the reaction was carried out for 60 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, and then the sieve was removed, washed, filtered, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. A Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 7.0 of water vapor and oxygen gas was introduced, and the reaction was carried out at 650°C for 1 hour. The total pressure in the reactor was controlled to 0.06 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain a Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.2 mol / L hydrochloric acid solution at 60°C for 170 minutes, controlling the solid-liquid mass ratio to 1:12 during treatment. A total of one treatment cycle was performed. After treatment, the solid was filtered and washed, and dried at 130°C for 4 hours to obtain the final Sn-Y molecular sieve product.
[0084] Comparative Example 2 NaY molecular sieves with a Na2O content of 12.0% (SiO2 / Al2O3 molar ratio of 4.8) were roasted at 500°C for 3 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Then, the NaY molecular sieves and tetramethylammonium bromide powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.042. The solid was then placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 185°C and the reaction was carried out for 70 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve, after quaternary ammonium cation exchange, was roasted at 530°C in air for 4 hours to obtain the HY molecular sieve. Then, the HY molecular sieve was placed in a stannous chloride solution, and the mass ratio of anhydrous stannous chloride in the solution to the HY molecular sieve was controlled to 0.07, and the solid-liquid mass ratio of the molecular sieve to the stannous chloride solution was set to 1:5, and the exchange was carried out at 90°C for 2 hours. After the ion exchange was completed, the solid was filtered and washed, and dried to obtain the Y molecular sieve Sn(II)Y after Sn ion exchange. A Sn(II)Y molecular sieve was placed in a tubular reactor, a mixed gas with a molar ratio of 7.0 of water vapor and oxygen gas was introduced, and the reaction was carried out at 650°C for 1 hour. The total pressure in the reactor was controlled to 0.06 MPa. After the process was completed, the introduction of gas was stopped, and after cooling, the sieve was removed to obtain a Sn-Y molecular sieve. The obtained Sn-Y molecular sieves were treated in a 0.2 mol / L hydrochloric acid solution at 60°C for 170 minutes, controlling the solid-liquid mass ratio to 1:12 during treatment. A total of one treatment cycle was performed. After treatment, the solid was filtered and washed, and dried at 130°C for 4 hours to obtain the final Sn-Y molecular sieve product.
[0085] Comparative Example 3 NaY molecular sieves with a Na2O content of 12.0% (SiO2 / Al2O3 molar ratio of 4.8) were roasted at 500°C for 3 hours, and tetramethylammonium bromide powder was dried at 110°C for 5 hours. Then, the NaY molecular sieves and tetramethylammonium bromide powder were crushed in a glove box and mixed uniformly, controlling the mass ratio of tetramethylammonium bromide to NaY molecular sieves to 0.042. The solid was then placed in a tubular furnace reactor, helium gas was introduced into the tubular furnace, and the inert gas in the reactor was maintained in a flow state. After replacing the gas in the reactor, the internal temperature was raised to 185°C and the reaction was carried out for 70 minutes. After the reaction was completed, the temperature was cooled in a helium atmosphere, then removed, washed, filtered, and dried to obtain Y molecular sieves after quaternary ammonium cation exchange. The Y molecular sieve, after quaternary ammonium cation exchange, was roasted at 530°C in air for 4 hours to obtain the HY molecular sieve. The HY molecular sieve was placed in a tubular furnace reactor, steam was introduced, and the reaction was carried out at 650°C for 1 hour, with the total pressure in the reactor controlled to 0.06 MPa. After the process was completed, the gas introduction was stopped, and after cooling, the sieve was removed to obtain the H-USY molecular sieve. The obtained H-USY molecular sieves were treated in a 0.2 mol / L hydrochloric acid solution at 60°C for 170 minutes, controlling the solid-liquid mass ratio to 1:12 during treatment. The treatment was performed once in total, and after treatment, the solid was filtered and washed, then dried at 130°C for 4 hours to obtain aluminum-free H-USY molecular sieves. Dealuminized H-USY molecular sieves were placed in a (NH4)2SnCl6 solution. The mass ratio of (NH4)2SnCl6 to HY molecular sieves in the solution was controlled to 0.07, and the solid-liquid mass ratio to 1:80. A certain amount of hydrochloric acid was added to control the concentration of hydrochloric acid in the solution to 0.1 mol / L. The reaction was carried out at 70°C for 24 hours, then filtered and dried, and roasted at 550°C for 4 hours to obtain Sn-Y molecular sieves. The structural properties of the molecular sieves produced in the above examples and comparative examples are shown in Table 1 below.
[0086] [Table 1] Note: In Table 1, the silicon-aluminum ratio refers to the SiO2 / Al2O3 molar ratio.
[0087] [Table 2] Note: In the continuation of Table 1, the silicon-aluminum ratio refers to the SiO2 / Al2O3 molar ratio.
[0088] Test Example 1 This test example demonstrates the performance of the molecular sieve according to the present invention in the Bayer-Villiger oxidation reaction of cyclohexanone. The performance of the Sn-Y molecular sieve in the examples and comparative examples was evaluated using the Bayer-Villiger oxidation reaction of cyclohexanone and tert-butyl hydroperoxide (TBHP). The reaction was carried out in a round-bottom flask equipped with a condensate cooler. 250 mg of catalyst was weighed and added to the flask, followed by 5 mmol of cyclohexanone, 3 mmol of TBHP (3.0 mol / L decane solution), and 10 mL of 1,4-dioxane (solvent). The reaction mixture was left in an oil bath at 85°C for 5 hours. After the reaction was complete, the mixture was transferred to ice water and cooled to room temperature. 0.4 g of chlorobenzene was added as an internal standard, and after homogeneous stirring, the mixture was centrifuged. The supernatant was analyzed by gas chromatography to evaluate the conversion rate of cyclohexanone, the selectivity of the target product ε-caprolactone, and the yield. The evaluation results are shown in Table 2.
[0089] [Table 3]
[0090] Test Example 2 This test example demonstrates the performance of the molecular sieve according to the present invention in the Bayer-Villiger oxidation reaction of 2-adamantanone. The performance of the Sn-Y molecular sieve in the examples and comparative examples was evaluated using the Bayer-Villiger oxidation reaction of 2-adamantanone and tert-butyl hydroperoxide (TBHP). The reaction was carried out in a round-bottom flask equipped with a condensate cooler. 550 mg of catalyst was weighed and added to the flask, followed by 4 mmol of 2-adamantanone, 3 mmol of TBHP (6.0 mol / L decane solution), and 10 mL of 1,4-dioxane (solvent). The reaction mixture was left in an oil bath at 93°C for 3 hours. After the reaction was complete, the mixture was transferred to ice water and cooled to room temperature. 0.4 g of cyclohexanone was added as an internal standard, and after homogeneous stirring, the mixture was centrifuged. The supernatant was analyzed by gas chromatography to evaluate the conversion rate of 2-adamantanone, the selectivity of the target product lactone, and the yield. The evaluation results are shown in Table 3.
[0091] [Table 4]
[0092] Combining the product characteristics in Table 1 with the evaluation results in Tables 2 and 3, it was found that the Sn active species of the Sn-Y molecular sieve according to the present invention are mainly distributed on the outer surface of the molecular sieve and have a relatively high L acid content. When catalyzing the oxidation reaction of cyclohexanone, this molecular sieve is advantageous in improving the conversion rate of cyclohexanone and the selectivity of the target product, ε-caprolactone, resulting in a relatively high yield of ε-caprolactone. When catalyzing the oxidation reaction of 2-adamantanone, it exhibits relatively high activity and selectivity, demonstrating excellent catalytic performance.
Claims
1. A Sn-Y type molecular sieve characterized by having a surface silicon-tin molar ratio of 50 to 70 and a bulk silicon-tin molar ratio of 200 to 300.
2. The molecular sieve has a surface silicon-tin molar ratio of 55 to 65 and a bulk silicon-tin molar ratio of 230 to 280. Preferably, the bulk SiO of the molecular sieve 2 / Al 2 O 3 The molar ratio is 60 to 140, preferably 80 to 120. Preferably, SiO on the surface of the molecular sieve 2 / Al 2 O 3 The molecular sieve according to claim 1, wherein the molar ratio is 350 to 700, preferably 420 to 630.
3. The molecular sieve according to claim 1, wherein the L-acid content measured by pyridine adsorption infrared spectroscopy at a desorption temperature of 200°C is 100 to 200 μmol / g, preferably 130 to 170 μmol / g.
4. The molecular sieve according to claim 1, wherein the ratio of L acid / B acid content measured by pyridine adsorption infrared spectroscopy at a desorption temperature of 200°C is 90 to 130, preferably 110 to 120.
5. The specific surface area of the molecular sieve is 770 to 850 m². 2 / g, preferably 790 to 830m 2 / g, The molecular sieve according to claim 1, and / or, the pore volume of the molecular sieve is 0.36 to 0.43 mL / g, preferably 0.37 to 0.41 mL / g.
6. The molecular sieve according to any one of claims 1 to 5, wherein the relative crystallinity of the molecular sieve is 86 to 96%, preferably 89 to 93%.
7. A method for producing an Sn-Y type molecular sieve, Step 1) involves subjecting a NaY molecular sieve to solid-phase ion exchange with an ammonium salt, and then roasting it to obtain an HY molecular sieve. Step 2) involves subjecting the HY molecular sieve to solid-phase ion exchange with a tin source to obtain a Y molecular sieve after Sn ion exchange, A method for producing an Sn-Y type molecular sieve, comprising step 3) treating the Y molecular sieve after Sn ion exchange in a mixed gas containing water vapor and oxygen gas, and then treating it with acid.
8. In step 1), the Na in the aforementioned NaY molecular sieve 2 O mass fraction is 10.5 to 12%, preferably 10.8 to 11.7%, Preferably, the SiO of the NaY molecular sieve. 2 / Al 2 O 3 The method according to claim 7, wherein the molar ratio is 4.8 to 5.7, preferably 5 to 5.
5.
9. The method according to claim 7, wherein the ammonium salt is at least one selected from organic quaternary ammonium salts, preferably at least one of tetramethylammonium bromide, tetramethylammonium chloride, tetraethylammonium bromide, tetraethylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium chloride, propyltrimethylammonium bromide, and propyltrimethylammonium chloride, more preferably tetramethylammonium bromide and / or tetramethylammonium chloride.
10. The mass ratio of the amount of ammonium salt to the amount of NaY molecular sieve used is 0.04 to 0.14, preferably 0.07 to 0.
1. Preferably, the conditions for the solid-phase ion exchange in step 1) include a reaction temperature of 140 to 190°C, preferably 160 to 170°C, under an inert atmosphere, and a reaction time of 60 to 180 min, preferably 100 to 140 min. Preferably, the roasting conditions in step 1) include a roasting temperature of 500 to 550°C and a roasting time of 3 to 6 hours in an oxygen-containing atmosphere. Preferably, the method according to any one of claims 7 to 9, further comprising the step of independently drying and / or roasting the NaY molecular sieve and the ammonium salt before performing the solid-phase ion exchange.
11. In step 2), the mass ratio of the tin source to the HY molecular sieve is 0.07 to 0.15, preferably 0.1 to 0.
12. Preferably, in step 2), the conditions for the solid-phase ion exchange include, under an inert atmosphere, a reaction temperature of 250 to 350°C, preferably 270 to 330°C, and a reaction time of 60 to 180 min, preferably 100 to 140 min. Preferably, the tin source is an anhydrous tin source, more preferably a divalent tin source, and even more preferably at least one of stannous chloride, stannous sulfate, and stann(II) acetate, according to any one of claims 7 to 10.
12. In step 3), the molar ratio of water vapor to oxygen gas in the mixed gas is 7 to 9, preferably 7.5 to 8.
5. Preferably, in step 3), the conditions for processing in a mixed gas containing water vapor and oxygen gas include a reaction temperature of 550 to 650°C, preferably 580 to 620°C, a processing time of 1 to 4 hours, preferably 2 to 3 hours, and a total pressure of 0.05 to 0.15 MPa, preferably 0.08 to 0.12 MPa, according to any one of claims 7 to 11.
13. Step 3) The acid is an inorganic acid and / or an organic acid, the inorganic acid is preferably at least one of nitric acid, hydrochloric acid, and sulfuric acid, and the organic acid is preferably at least one of citric acid, oxalic acid, EDTA, and tartaric acid. Preferably, the concentration of the acid used in the acid treatment is 0.2 mol / L to 0.4 mol / L, preferably 0.25 to 0.35 mol / L. Preferably, the conditions for the acid treatment include a treatment temperature of 30 to 60°C, preferably 40 to 50°C, a treatment time of 60 to 180 min, preferably 100 to 140 min, and a solid-liquid mass ratio in the acid treatment of 1:6 to 1:12, preferably 1:8 to 1:10, according to any one of claims 7 to 12.
14. Use of the Sn-Y type molecular sieve according to any one of claims 1 to 6 in the oxidation reaction of a cyclic ketone, preferably in the oxidation reaction of at least one of cyclohexanone, 2-adamantanone, dihydrocarbone, and bicyclo[3,2,0]hepta-2-en-6-one.
15. A method for the oxidation reaction of a cyclic ketone, comprising the step of reacting a cyclic ketone with an oxidizing agent under oxidation conditions and in the presence of a solvent and a catalyst, wherein the catalyst is an Sn-Y type molecular sieve as described in any one of claims 1 to 6. Preferably, the cyclic ketone is at least one of cyclohexanone, 2-adamantanone, dihydrocarbone, and bicyclo[3,2,0]hepta-2-en-6-one, more preferably cyclohexanone and / or 2-adamantanone. Preferably, the oxidizing agent is at least one selected from tert-butyl hydroperoxide, hydrogen peroxide, cumene hydroperoxide, cyclohexyl hydroperoxide, peracetic acid, and perpropionic acid, preferably tert-butyl hydroperoxide. Preferably, the molar ratio of the oxidizing agent to the cyclic ketone is 1:(1-3). Preferably, the amount of catalyst used is 80 to 600 mg per 1 mmol of oxidizing agent. Preferably, the conditions for the oxidation reaction include an oxidation reaction temperature of 75 to 95°C and an oxidation reaction time of 2 to 8 hours, characterized in that a method for oxidizing a cyclic ketone.